Morphometric analysis of supraorbital foramen in South Indian dry skulls with its clinical implications in craniofacial surgeries - Vikram Palimar; Chandni Gupta (Journal of Krishna Institute of Medical Sciences University, 2022)
Background: Knowing the location of supraorbital foramen and notch is very important as it transmit supraorbital vessels and nerve and they can get damage while doing several surgeries like eyebrow lift surgery and treating facial wounds. Aim and Objectives: To find out the occurrence of supraorbital notches and foramina in adult skull, dimensions of foramen and to locate its distance from the nasion. Material and Methods: The study was carried out on 50 dry skulls. Measurements of supraorbital foramen were taken from the nasion on both sides of the skull. Presence or absence of notch and foramen was also noted. Dimensions of foramen were also noted. Data analysis was done by using the Statistical Package for Social Sciences (SPSS) 19 version. Results: The mean distance of the supraorbital foramen to the nasion was 2.39, 2.29 cm on the right and left side respectively. The mean width of the foramen was 6.36, 5.36 mm on the right and left side respectively. The mean height of the foramen was 2.7, 3.10 mm on the right and left side respectively.Bilateral notch was present in 38% of skulls, bilateral foramen was seen in 22% of skulls, one side notch and one side foramen was seen in 34% of skulls and both side supraorbital notch was absent in 6% of skulls. On right and left side notch, foramen was present in 54% and 56%, 40% and 38% of skulls. Conclusion: Knowing the location of supraorbital foramen and notch is very important as it transmits the supraorbital vessels and nerve and they can get damaged while doing several surgeries like eyebrow lift surgery and treating facial wounds.